A Dual Focus Approach: Unveiling Drug Consumption Patterns and AMR Reduction Strategies in India's Small Dairy Sector - Neetha SS, Nitin Ubale, Jai rakash gupta (Revista Electronica de Veterinaria, 2024)
The production of livestock, especially dairy products, is crucial to the food and nutritional security of Indian communities. It boosts the nation's economy and provides wages for an enormous number of farmers. In India, antimicrobial resistance (AMR) microorganisms pose a major threat to public health, a country that consumes a great deal of antibiotics. The objectives of this study were to assess prior AMR-mitigation methods, highlight medication usage and animal health practices that can be contributing to the establishment and spread of AMR in the nation that discuss the Theory of Change (TOC) as a method for influencing the selection of alternatives. We identified activities in India that have the possibility of facilitating the development and dissemination of resistant antibiotics. We conducted a review of the literature using PubMed, Google Scholar and Google then summarized as well as reviewed the findings by categories. One thousand studies from three distinct sources were found after a thorough review of the literature. After rigorous screening and meeting qualifying standards, thirty papers were included in the final analysis. Inadequate infrastructure supports the delivery of services and animal disease surveillance is not as advanced. Services for animal health are provided by a number of entities. Farmers therefore, take care of their animals and seek consultation when an animal's condition becomes unresponsive to therapy. Antibiotics are employed when treating mastitis instances. There is little evidence of drug withdrawal periods and there have been reports of antibiotic-contaminated milk. This study addresses different medication usage and animal health behaviors that result in AMR and recommends that stakeholders engage in a TOC exercise to support treatments that prioritize animal health and investigate adoption incentives.